2005
DOI: 10.1109/tia.2005.847312
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Flux Weakening in Surface PM Machines Using Fractional-Slot Concentrated Windings

Abstract: Abstract-A design approach is presented for achieving optimal flux-weakening operation in surface permanent-magnet (SPM) synchronous machines by properly designing the machine's stator windings using concentrated, fractional-slot stator windings. This technique makes it possible to significantly increase the machine inductance in order to achieve the critical condition for providing wide speed ranges of constant-power operation. The conditions for optimal flux weakening can be achieved while simultaneously del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(109 citation statements)
references
References 20 publications
3
105
0
1
Order By: Relevance
“…To completely cancel the flux, the current is called short-circuit current I sc . This principle has been shown on the Figure 5 [ Soong et al, 2002;Ef-Refaie et al, 2005;Nguyen et al, 2010;Zhu et al, 2006]. According to Figure 4, the torque-speed characteristic of the driving cycle of the vehicle has shown that there are points where the speed is higher than the base speed (1820 rpm).…”
Section: Flux-weakening Copper Lossesmentioning
confidence: 95%
“…To completely cancel the flux, the current is called short-circuit current I sc . This principle has been shown on the Figure 5 [ Soong et al, 2002;Ef-Refaie et al, 2005;Nguyen et al, 2010;Zhu et al, 2006]. According to Figure 4, the torque-speed characteristic of the driving cycle of the vehicle has shown that there are points where the speed is higher than the base speed (1820 rpm).…”
Section: Flux-weakening Copper Lossesmentioning
confidence: 95%
“…A value of 2/5 was selected [1] because it offers a high winding factor for good utilization of the permanent magnets, provides a large leakage reactance to produce good field-weakening characteristics, and results in low cogging torque.…”
Section: A Machine Design Processmentioning
confidence: 99%
“…However recent work on fractional-slot pitch, concentrated winding (FSCW) surface PM machines has shown that these machines have high values of stator leakage inductance which allows them to achieve a wide constant power speed range (CPSR) [1]. This type of machine has potential for demanding traction applications requiring wide CPSR, high power density and high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent magnet synchronous machines (PMSM) with concentrated winding topologies have recently become popular due to simpler and more compact structure as well as some operational advantages such as wider flux weakening range and higher torque output [1,2,8]. Furthermore magnetic isolation feature between coils, which naturally comes with concentrated winding topology, presents some opportunities such as better fault tolerance [3,4] and multi tasked operation as required by some accessory drive system applications in HEVs.…”
Section: Introductionmentioning
confidence: 99%